Cyclic Microwave-Assisted Metathetic Synthesis of SPION/Ca3V2O8:Er3+,Yb3+ Nanocomposites and Their Optical Properties - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
Er3+/Yb3+ co-doped Ca3V2O8 (Ca3V2O8:Er3+/Yb3+) nanocomposites with superparamagnetic iron oxide nanoparticles (SPIONs) have been successfully synthesized by a cyclic microwave-assisted metathetic method followed by heat-treatment. The microstructure exhibited well-defined and homogeneous morphology with the Ca3V2O8:Er3+/Yb3+ particle size of 1-2 μm and Fe3O4 particle size of 100-500 nm. The Fe3O4 nonoparticles were self-preferentially crystallized and immobilized on the surface of Ca3V2O8:Er3+/Yb3+ particles. The synthesized SPION/Ca3V2O8:Er3+/Yb3+ nanocomposites were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Other optical properties were also examined using photoluminescence emission measurements and Raman spectroscopy.